2017
DOI: 10.1016/j.anr.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Decisional Conflict Scale for Evaluating Advance Care Decision Conflict in Community-dwelling Older Adults

Abstract: The K-DCS appears to be a valid measure to evaluate decisional conflict about advance directives in community-dwelling Korean older adults. Further validation of the K-DCS is warranted, though caution should be exercised in using subscales because of differences in decisional contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…In this study, we used a reliable, previously confirmed, and valid scale (i.e., DCS) for the primary outcome, and a nonequivalent control group that controlled for internal validity [21,26,27]. A feature of a nonequivalent control group design is that both naturally occurring groups will be similar.…”
Section: Plos Onementioning
confidence: 99%
“…In this study, we used a reliable, previously confirmed, and valid scale (i.e., DCS) for the primary outcome, and a nonequivalent control group that controlled for internal validity [21,26,27]. A feature of a nonequivalent control group design is that both naturally occurring groups will be similar.…”
Section: Plos Onementioning
confidence: 99%
“…The K-AD model was employed in both public and clinical settings using samples of community-dwelling older people (J. Kim, Kim, Hong, Kang, & An, 2017) and patients with largely solid cancers with their family as caregivers (S. Kim, Koh, Park, & Kim, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…All except one [17] of the studies (Table 2) assessed internal consistency and determined Cronbach's a or KudereRichardsone20 (KR-20) values. One study [12] provided only Cronbach's a for the total items, despite the instrument comprising three subscales.…”
Section: Internal Consistencymentioning
confidence: 99%
“…In the study involving the Korean version of the Decisional Conflict Scale (K-DCS) [17], Cronbach's a was assessed using the original 16-item DCS comprising five subscales, and three subscales satisfied internal consistency. EFA was performed using only the nine items that satisfied internal consistency of the three subscales, and the K-DCS was extracted comprising two subscales (and this was not followed by determining Cronbach's a for the newly extracted two subscales in a Korean population).…”
Section: Internal Consistencymentioning
confidence: 99%
See 1 more Smart Citation